Rapid extraction and separation of indium(III) with a high molecular weight amine - Shilmkar, T. N.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Indian Journal of Chemical Technology, 2008)
The liquid-liquid extraction of indium(III) from sodium succinate media using n-octylaniline in toluene as an extractant was studied. Quantitative extraction of indium(III) was observed in the range of 0.004-0.0075 M sodium succinate at pH 3.8-6.0 with 4% n-octylaniline in toluene. Indium(III) was completely stripped from the metal loaded organic phase of the extractant with water and determined complexometrically. The stoichiometry of the extracted species was determined on the basis of;slope analysis. The extraction was found to proceed by a ion-pair mechanism with the extracted species being [RNH3+In(succinate)(2)(-)](org). Separation of indium(III) was carried out from some associated metals like Tl(I), Mg(II), Ni(II), Cu(II), Zn(II),. Cd(II), Hg(II), Pb(II), GC(IV), Sb(III), Bi(III). The selectivity of the extraction of indium(III) can also be achieved by use of a suitable masking agent for estimation and determination from the synthetic mixture corresponding to alloy to show the practical utility of the extractant.
Keywords: Indium(III); n-octylaniline; Separation; solvent extraction; succinate

Rapid liquid-liquid extraction of thallium(III) from succinate media with 2-octylaminopyirdine in chloroform as the extractant - Mahamuni, Sandip V.; Wadgaonkar, Prakash P.; Anuse, Mansing A. (Journal of the Serbian Chemical Society, 2008)
A simple solvent extraction study of thallium(III) was conducted. Selective and quantitative extraction of thallium(III) by 2-octylaminopyridine (2-OAP) in chloroform occurred from aqueous sodium succinate medium (0.0075 M) at pH 3.0. Thallium(III) was back extracted with acetate buffer (pH 4.63). The effect of the concentration of succinate and 2-OAP, the role of various diluents, stripping agents, loading capacity of 2-OAP, equilibrium time and aqueous:organic volume ratio on the extraction of thallium(III) was studied. The stoichiometry of the extracted species was determined based on the slope analysis method and found to be 1: 2: 1 (metal: acid: extractant). The temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions Delta H, Delta G and Delta S for the extraction reaction. The method is free from interference of a large number of cations and anions. The method was used for the selective extraction of thallium(III) from its binary mixture with Zn(II), Cd(II), Hg(II), Bi(ill), Pb(II), Se(IV), Te(IV), Sb(III), Ga(III), In(III), AI(III), TI(I) and Fe(III). The proposed method was applied to the synthetic mixtures and alloys. It is simple, selective, rapid and eco-friendly.
Keywords: 2-OAP; liquid-liquid extraction; succinate media; Temperature effect; thallium(III)

Solvent extraction of trivalent indium from succinate solution by 2-octylaminopyridine in chloroform - Mahamuni, Sandip V.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Journal of the Iranian Chemical Society, 2009)
Extraction processes of indium(III) with 2-octylaminopyridine (2-OAP) from media of various complexing ability, succinate and salicylate, in chloroform have been elucidated. The ion-pair complex has also quantitative extraction in xylene and 1,2-dichloroethane. Indium(III) from organic phase was stripped with 1.0 M hydrochloric acid and determined complexometrically with EDTA. The stoichiometry of the extracted species was found out on the basis of slope analysis. The extraction of indium(III) proceeds by an anion exchange mechanism and the extracted species is [RR'NH(2)(+)In(succinate)(2)(-)]((org)). Temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions (Delta H, Delta G and Delta S) for extraction reaction. It is possible to separate indium(III) from Zn(II), Cd(II), Pb(II), Hg(II), Bi(III), Tl(I), Tl(III), Ga(III), Al(III), Te(IV), Se(IV), Sb(III), Fe(III) and Sn(IV). The method is simple, rapid and reproducible and can be used to determine the indium from samples like alloys.
Keywords: 2-OAP; Binary separations; Indium(III); liquid-liquid extraction; Sodium succinate

Liquid-liquid extraction and recovery of gallium(III) from acid media with 2-octylaminopyridine in chloroform: analysis of bauxite ore - Mahamuni, Sandip V.; Wadgaonkar, Prakash P.; Anuse, Mansing A. (Journal of the Serbian Chemical Society, 2010)
The liquid liquid extraction of gallium(III) from hydrochloric acid solution using 2-octylaminopyridine (2-OAP) in chloroform was investigated. The extraction of gallium(III) from 6.0-9.0 mol dm(-3) hydrochloric acid was found to be quantitative using 0.033 mol dm-3 2-OAP in chloroform. The effect of the reagent concentration and other parameters on the extraction of gallium(111) was also studied. The stoichiometry of the extracted species of gallium(In) was determined based on the slope analysis method. The extraction reaction proceeded via the anion exchange mechanism from hydrochloric acid and the extracted species was [RR'NH(2)(+)GaCl(4)(-)](org). The extraction of gallium(III) was performed in the presence of various ions to ascertain the tolerance limit to individual ions. The temperature dependence of the extraction equilibrium constants was examined to estimate the apparent thermodynamic functions (Delta H, Delta S and Delta G) for the extraction reaction. Gallium(III) was successfully separated from commonly associated metal ions, such as Zn(II), Pb(II), Cd(II), Hg(II), Bi(III), Al(III), Se(IV), Sb(III), Sn(IV), In(III), TI(I) and TI(III). However, gallium(III) was separated from Fe(III) from weak organic acid media. The procedure was also extended to the determination of gallium(III) in bauxite ore by the standard addition method.
Keywords: 2-OAP; gallium(III); liquid-liquid extraction; recovery of gallium from bauxite

Adsorption of toxic Pb(II) on activated carbon derived from agriculture waste (Mahogany fruit shell): isotherm, kinetic and thermodynamic study - Patil, Suryakant A.; Suryawanshi, Umesh P.; Harale, Namdev S.; Patil, Sandip K.; Vadiyar, Madgonda M.; Luwang, Meitram N.; Anuse, Mansing A.; Kim, Jin H.; Kolekar, Sanjay S. (International Journal of Environmental Analytical Chemistry, 2022)
An adsorbent, mahogany fruit shell activated carbon(MFSAC), was derived from environmental friendly raw material, i.e. agriculture waste and explored for bench scale adsorption of toxic Pb(II). A facile MFSAC material was synthesised using a chemical activation method using concentrated sulphuric acid as an impregnating (activating) reagent. So derived adsorbent material was characterised by FTIR, XRD, BET, SEM, EDAX, TGA and XPS techniques to know the properties and plausible adsorption mechanism. Bench scale adsorption of toxic Pb(II) and maximum adsorption capacity of MFSAC were exhibited through batch adsorption experiments. The effect of physico-chemical parameters such as pH (1-7), MFSAC amount (0.5-5.0 g L-1), Pb(II) concentration (200-1000 mgL(-1)), contact period (60-600 min) and orbital shaking speed (60-200 rpm) was studied for maximum removal of Pb(II) upto 99.70 +/- 0.17%. The experimental data follow the Langmuir adsorption isotherm with a maximum monolayer adsorption capacity 322.28 mg g(-1)and pseudo-second-order kinetic uptake rate. The thermodynamic and temperature study revealed that the adsorption process was spontaneous and endothermic in nature (Delta H-o = 43.37 kJ mole(-1), Delta S-o = 158.02 J mol(-1)K(-1)). Most importantly, the MFSAC adsorbent was successfully regenerated and reused with conspicuous performance up to five consecutive cycles. The bench-scale adsorption with simple synthesis route, good stability and remarkable regeneration capability makes the MFSAC as an encouraging adsorbent for wastewater treatment.
Keywords: activated carbon; Adsorption; mahogany fruit shell; Pb(II); sulphuric acid